Contemporary Sinhalese Buddhism in its relation to the Pali canon - Gombrich, R; Gombrich, Richard (1969)
This thesis is based on a study of classical Pali texts and of materials gathered during a year spent in a village in central Ceylon. The material consists in particular of interviews with monks living in nearby village monasteries. My notes of these interviews, which cover more topics than could be discussed in the thesis, are reproduced in Appendix One, and some of my printed materials are summarily presented in Appendix Two. The circumstances of my field work are detailed in the last part of the Introduction. Factually, the thesis aims to give an account of the religious beliefs and ethos of Sinhalese (Kandyan) Buddhist villagers, expressed as far as possible in their own terms. As explained in chapter 1, Buddhism is a system of belief almost exclusively concerned with liberation from this world. It is therefore necessarily secretive, requiring supplementation by beliefs concerning other matters. Beliefs about Gods and demons and how they can help or hinder human beings which to a Western observer fall within the domain of religion are not seen in these terms by Buddhists. These are therefore only examined in so far as they are relevant to the understanding of Buddhism. Issue is taken, on the other hand, with the Western interpretation of Buddhism as an essentially nonreligious philosophy. Chapter 2 introduces the terms used by my informants in talking about their beliefs and institutions. The arrangement of chapters 3 to 8 is in some measure due to the formulation of the Buddhists themselves: they consider Buddhism in terms of the Three Jewels, which are the Buddha, the Doctrine, and the Order of monks, while their doctrinal emphasis is on the operation of karma and on ethical questions. Chapter 3 deals with the Buddha, chapter 4 with karma and the arrangement of the universe, chapter 5 with some problem in the doctrine of karma, chapter 6 with ethics, and chapters 7 and 8 with problems primarily concerning the Order. On the theoretical level the thesis is largely concerned with the interaction of belief and behaviour as an agent of religious change. My problem and concepts are presented in the first part of the Introduction. Although the general tenor of the thesis is to show that Sinhalese Buddhism has been remarkably conservative, if it is compared with the Pali Canon and its commentaries, there have been changes, and I suggest that some at least have arisen because of discrepancies between what people say and what they do: behaviour has affected doctrine, which in turn has affected behaviour. There are still in the religion as observable to-day discrepancies between what people eay and what they do; the thesis attempts to record both statement and performance, and suggests further that statements may vary with the context. Finally the thesis proposes that an acquaintance with Ceylonese Buddhism as a living system may provide insight into the workings of early Buddhism as described in the classical texts. In particular the last chapter suggests that scholars relying on texts and preconceptions have over-drawn the distinction between monks and laity as moral agents, and between Theravada and Mahayana Buddhism as ethical systems.